2021
DOI: 10.1007/s12288-021-01428-7
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Transfusion-Transmitted Hepatitis E Virus: Evidence from Seroprevalence Screening of Blood Donations

Abstract: Throughout the world, there has been growing concern over the risk of hepatitis E virus (HEV) transmission via blood transfusion. The present study screened blood donor samples for anti-HEV immunoglobulin M (IgM) and immunoglobulin G (IgG). The prevalence of HEV infection was assessed on a total of 1,003 archived serum samples obtained from the National Blood Centre, Malaysia. The samples were collected from healthy blood donor from Klang Valley between 2017 and 2018. All samples were tested for IgM and IgG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
2
6
0
1
Order By: Relevance
“…The ethnic disparities in the HEV IgG seroprevalence rate found in this study are also in concordance with those previously reported in Malaysia (21). This study found that of the three major ethnic groups in Malaysia, the majority of HEV IgG seropositivity occurred among people of Chinese descent, and only two Malay men were found to be positive for anti-HEV IgG antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…The ethnic disparities in the HEV IgG seroprevalence rate found in this study are also in concordance with those previously reported in Malaysia (21). This study found that of the three major ethnic groups in Malaysia, the majority of HEV IgG seropositivity occurred among people of Chinese descent, and only two Malay men were found to be positive for anti-HEV IgG antibodies.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of HEV PCR positivity rates of blood donors worldwide [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]; Table S2. Studies of HEV seroprevalence of blood donors worldwide [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70...…”
unclassified
“…In our previous study on serum samples of blood donors, none of the Malay blood donors were found to be positive for IgG or IgM against HEV. 27 This could also be a contributing factor to the absence of IgG and IgM HEV antibodies in the current study samples.…”
Section: Discussionmentioning
confidence: 84%
“… 26 Most recently, in 2020, HEV-specific IgG antibodies were detected in 3.1% and IgM in 0.9% of blood donor samples in Malaysia. 27 Of note, the prevalence of HEV viraemia varies among global blood donors. The overall rates of anti-HEV IgG reactivity among blood donors in Europe ranged from 4.7% to 52.5%.…”
Section: Introductionmentioning
confidence: 99%